Microdroplet Protocells: Self‐Organizing Microdroplet Protocells Displaying Light‐Driven Oscillatory and Morphological Evolution (Small 23/2021). Issue 23 (10th June 2021) - Cheng, Gong; Lin, Chenyu; Perez‐Mercader, Juan
Abstract : In article number 2101162, Gong Cheng, Chenyu Lin, and Juan Perez‐Mercader demonstrate that under the influx of external energy, active microdroplet protocells sustain a range of life‐like complex nonequilibrium behaviors driven by dynamic degradation/formation of molecular building blocks. They exhibit oscillatory growth and shrinkage, and the formation of a variety of dynamic and higher‐order biomimetic microstructures.